Training and Self Efficacy: Key to Improve Technological Pedagogical and Content Knowledge of Economics Teachers - Kodri,; Suwatno,; Machmud, Amir (International Journal of Psychosocial Rehabilitation, 2020)
The influence of training and self-efficacy on the Technological Pedagogical and Content Knowledge (TPACK) of Economics Teachers in Indonesia is analyzed in this study. An Explanatory survey method and data collection techniques through questionnaires to Teachers with a major of Economic is uses this study. Total population of 472 economics teachers in Greater Bandung, West Java, Indonesia, proportional sampling technique obtained 217 respondents. The collected data were using a descriptive analysis. Then, we also analyzed using a structural equation modelling (SEM). The results of this study indicate that training has a positive influence on teacher TPACK, self- efficacy has a positive influence on teacher TPACK as well as training and self-efficacy has a positive influence on teacher TPACK. The implication of this research is to be able to increase TPACK, gurus must improve training and self-efficacy.